2005
DOI: 10.1039/b502097b
|View full text |Cite
|
Sign up to set email alerts
|

A systematic investigation of aluminium ion speciation at high temperature. Part. 1. Solution studies

Abstract: Speciation diagrams of aluminium ions in aqueous solution (0.2 M) at high temperature (90 degrees C) have been obtained from 48 h time-resolved multi-batch titration experiments monitored by 27Al NMR spectroscopy, potentiometry and dynamic light scattering. The quantitative speciation patterns and kinetic data obtained offer a dynamic picture of the distribution of soluble and insoluble Al species as a function of hydrolysis ratio h(h=[OH-]/[Al3+]) over a very broad range of conditions (-1.0 < or =h < or = 4.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
54
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(63 citation statements)
references
References 29 publications
6
54
0
3
Order By: Relevance
“…Although there are a few reports on Al 30 species, and a great deal of progress has been achieved, most of these investigations were carried out in diluted solutions and were aimed to structural characterization. Shafran et al [27,28] have studied the Al speciation in medium concentration at high temperature using improved 27 Al NMR quantification method. To date, much less was concerned on the formation and transformation of Al 30 species in highly concentrated HPA solutions (0.2-2.0 mol L −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although there are a few reports on Al 30 species, and a great deal of progress has been achieved, most of these investigations were carried out in diluted solutions and were aimed to structural characterization. Shafran et al [27,28] have studied the Al speciation in medium concentration at high temperature using improved 27 Al NMR quantification method. To date, much less was concerned on the formation and transformation of Al 30 species in highly concentrated HPA solutions (0.2-2.0 mol L −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The structure of e-Al 13 is highly symmetric with a central tetrahedral fourfold coordinated Al +3 surrounded by 12 octahedral coordinated Al 3+ . The e-Al 13 is usually synthesised in an Al 3+ solution by titrating with NaOH or KOH [1][2][3][4][5][6]. Recently, the homogenous hydrolysis of Al 3+ solution by the decomposition of urea [7] and the supramolecular selfassembled methods were also used for the e-Al 13 preparations [8].…”
Section: Introductionmentioning
confidence: 99%
“…Al 30 , with 2 nm in length (Phillips et al, 2003), was the largest Al polycation that was identified in polyaluminum solution. Al 30 formed by further polymerizing two Al 13 and four Al monomers under hydrothermal treatment (Allouche and Taulelle, 2003;Shafran and Perry, 2005a). Al 30 species was more thermal resistant and more stable in low pH solution than Al 13 species (Chen, 2006;Chen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%